Assessment of PM2.5-bound nitrogen-containing organic compounds (NOCs) during winter at urban sites in China and Korea. (October 2020) - Jang, Kyoung-Soon; Choi, Mira; Park, Minhan; Park, Moon Hee; Kim, Young Hwan; Seo, Jungju; Wang, Yujue; Hu, Min; Bae, Min-Suk; Park, Kihong
Abstract: In this study, ambient fine particles (PM2.5 ) were collected in two urban cities in China and Korea (Beijing and Gwangju, respectively) simultaneously in January 2018. Analysis of the nonpolar and semipolar organic matter (OM) using atmospheric pressure photoionization (APPI) Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) revealed that compounds containing only C, H, and O (CHO) and those containing C, H, O, and N (CHON) accounted for more than 90% of the total intensity of the OM peaks. Higher proportions of CHON compounds were observed during days with abnormally high PM2.5 concentrations at both sites than on regular or non-event days. The proportion of CHON species at the Beijing site was not correlated with secondary ionic species (i.e., NO3 −, SO4 2−, and NH4 + ) or gaseous components (i.e., O3, NO2, and SO2 ). In contrast, the proportion of CHON species at the Gwangju site was positively correlated with the concentrations of particulate nitrate and ammonium ions, assuming that ambient ammonium nitrate plays a role in the atmospheric formation of nitrogen-containing organic compounds (NOCs) at the Gwangju site and that Gwangju is more strongly influenced by secondary aerosols than Beijing is. In particular, a significant proportion of the compounds observed at the Beijing site contained only C, H and N (CHN), while negligible amounts of CHN were detected at the Gwangju site. The CHN species in Beijing were identified as quinoline compounds and the corresponding –CH2 homologous series using complementary GC × GC-TOF MS analysis. These results suggest that NOCs and their –CH2 homologous series from primary emissions may be significant contributors to nonpolar and semipolar OM during winter in Beijing, while NOCs with high oxidation states, likely formed via ambient-phase nitrate-mediated reactions, may be the dominant OM constituents in Gwangju. Graphical abstract: Image 1 Highlights: Site-specific differences in the airborne nitrogen-containing organics were observed. Nitrogen-containing organics may be significant contributors of the organic matter. The compounds containing only C, H and N were identified as quinoline compounds. The regional characteristics will be utilized further for the source apportionment.